Peripheral blood leukocyte subpopulation dynamics during Trypanosoma congolense infection in Boran and N'Dama cattle. An analysis using monoclonal antibodies and flow cytometry - Ellis, J.A.; Scott, J.R.; MacHugh, Niall D.; Gettinby, George; Davis, W.C. (Wiley, 1987)
Summary A panel of monoclonal antibodies (MoAb) with specificities for bovine leucocyte subsets were used in conjunction with routine haematological procedures to analyse sequential changes in peripheral blood leucocyte populations during the course of tsetse fly‐transmitted Trypanosoma congolense infection in trypanotolerant N'Dama and trypanosusceptible Boran cattle. Subsequent to the first parasitaemic wave, the N'Dama cattle maintained packed cell volumes (PCV) above 22 and lower levels of parasitaemia than Boran throughout the 160 days of the experiment. In contrast, the Borans developed severe anaemia and required curative drug therapy (i. e., PCV dropped to less than 15) by 55 days (range: 22–55 days) post infection. There were significant (P < 0±05) decreases in total white blood cells and total lymphocytes from pre‐infection levels to the first peak of parasitaemia (day 16 post‐infection) in both groups. Flow cytometric analyses using MoABs revealed that this change was due to an absolute decrease in T cells expressing BoT2 and either BoT4 or BoT8, surface immunoglobulin M‐positive (sIgM+) B cells, and null cells which did not express T cell, B cell or monocyte markers. During this period there was significant variation over time, but no overall increase or decrease, in the number of cells expressing class II major histocompatibility (MHC) molecules or monocyte markers, or in the number of circulating neutrophils or eosinophils. The BoT4/BoT8 ratios were significantly (P < 0±01) increased in both groups of infected animals at the first peak of parasitaemia. After day 22 in the infected N'Damas and in the Borans which required drug therapy, there was a leucocytotic response characterized by an increase in the total number of B cells, T cells, and null cells. Prior to infection and throughout the course of the experiment N'Dama cattle had significantly (P < 0±01) higher numbers of B cells and null cells than Boran.